2013
DOI: 10.1038/onc.2013.314
|View full text |Cite
|
Sign up to set email alerts
|

Stefin B deficiency reduces tumor growth via sensitization of tumor cells to oxidative stress in a breast cancer model

Abstract: Lysosomal cysteine cathepsins contribute to proteolytic events promoting tumor growth and metastasis. Their enzymatic activity, however, is tightly regulated by endogenous inhibitors. To investigate the role of cathepsin inhibitor stefin B (Stfb) in mammary cancer, Stfb null mice were crossed with transgenic polyoma virus middle T oncogene (PyMT) breast cancer mice. We show that ablation of Stfb resulted in reduced size of mammary tumors but did not affect their rate of metastasis. Importantly, decrease in tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…However, what happens if these control mechanisms are not in place, such as is observed in certain tumor cells which exhibit reduced or completely abolished expression of cytoplasmic cysteine protease inhibitors (Alvarez-Diaz et al 2009;Butinar et al 2014). In these cases, the proteolytic enzymes become enzymatically active in a cellular compartment in which they are otherwise supposed to remain inactive under healthy conditions.…”
Section: Endo-lysosomal Cysteine Peptidases: Myths and Common Questionsmentioning
confidence: 94%
“…However, what happens if these control mechanisms are not in place, such as is observed in certain tumor cells which exhibit reduced or completely abolished expression of cytoplasmic cysteine protease inhibitors (Alvarez-Diaz et al 2009;Butinar et al 2014). In these cases, the proteolytic enzymes become enzymatically active in a cellular compartment in which they are otherwise supposed to remain inactive under healthy conditions.…”
Section: Endo-lysosomal Cysteine Peptidases: Myths and Common Questionsmentioning
confidence: 94%
“…Interestingly, Lehtinen et al (60) showed that stefin B protects cerebellar granule neurons from the oxidative stress, and the stefin B deficiency resulted in the increased apoptosis in the cerebellum. In addition, Butinar et al (61) reported that stefin B-deficient tumor cells were significantly more sensitive to cell death upon the increased oxidative stress. Furthermore, Shimada et al (51) showed that staurosporin (STS), a pro-apoptotic protein kinase inhibitor, was sufficient to act as a second signal for the NLRP3 inflammasome activation.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…The role of stefin B has been examined in breast cancer with Stfb null mice (Butinar et al, 2014). In transgenic PyMT mice that were stefin B knockout no effect on proliferation, angiogenesis, migration, and spontaneous cell death was noted.…”
Section: Type I Cystatinsmentioning
confidence: 99%